If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + x + -2 = 0 Reorder the terms: -2 + x + 3y = 0 Solving -2 + x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + x + 2 + 3y = 0 + 2 Reorder the terms: -2 + 2 + x + 3y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x + 3y = 0 + 2 x + 3y = 0 + 2 Combine like terms: 0 + 2 = 2 x + 3y = 2 Add '-3y' to each side of the equation. x + 3y + -3y = 2 + -3y Combine like terms: 3y + -3y = 0 x + 0 = 2 + -3y x = 2 + -3y Simplifying x = 2 + -3y
| 20-9w=4(15-1) | | r+20r+r+20r= | | 12-y/2=8 | | 4(4a-8)+6a= | | -5[4y-11]-3=12 | | 8(2x+10)-12= | | 4(x+6)-2= | | 4d+1=2d+15 | | n+n+6n+6n= | | a+3a+a+3a= | | 5(x-4)=-15 | | 2[6-2x]-1=7 | | 8a+72=106.4 | | (2x-3)(4x+3)= | | 9x-5(x-2)=6 | | 4x^3-12x^2-52x+60=0 | | 5y-8=y-24 | | 19.2=6c-3 | | 7s+6y-3s+4y+15= | | (5+9i)+(3-2i)= | | 5x-6=2x+10 | | ln(7x-13)=ln(2x-17) | | 4=k+17 | | 3(a+1)-5=2a-7 | | -2[y-7]+18=8 | | x^2-95=-94 | | Y-2=-2(x-5) | | j^2-70=-61 | | d^2-81=0 | | 3[x+7]-14=4 | | g^2+66=70 | | 0=-5+3y-x |